2010
DOI: 10.1111/j.1654-109x.2009.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Life on the edge – to which degree does phreatic water sustain vegetation in the periphery of the Taklamakan Desert?

Abstract: Questions: Do the vegetation-specific patterns in the forelands of river oases of the Taklamakan Desert provide clues to the degree to which a vegetation type depends on unsaturated soil moisture, brought about by extensive floodings, or phreatic water? Location: Foreland of the Qira oasis on the southern rim of the Taklamakan Desert, Xinjiang Uygur Autonomous Region, China. Methods: A vegetation map was prepared using a SPOT satellite image and ground truthing. Measurements of soil water contents were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
(63 reference statements)
1
26
0
Order By: Relevance
“…By decreasing evaporation and improving moisture retention by canopy shading and organic matter accumulation, respectively (Pugnaire et al 1996, Kidron andGutschick 2013), benefactor plants can indirectly increase the water content of shallow soil. The spatial distribution of available moisture in shallow soil can also be directly influenced by the hydraulic lift of woody and herbaceous plants (Bruelheide et al 2010, Kizito et al 2012). However, target plants can be inhibited when soil moisture is negatively influenced by indirect effects, like canopy interception, or direct effects, like water competition.…”
Section: Introductionmentioning
confidence: 99%
“…By decreasing evaporation and improving moisture retention by canopy shading and organic matter accumulation, respectively (Pugnaire et al 1996, Kidron andGutschick 2013), benefactor plants can indirectly increase the water content of shallow soil. The spatial distribution of available moisture in shallow soil can also be directly influenced by the hydraulic lift of woody and herbaceous plants (Bruelheide et al 2010, Kizito et al 2012). However, target plants can be inhibited when soil moisture is negatively influenced by indirect effects, like canopy interception, or direct effects, like water competition.…”
Section: Introductionmentioning
confidence: 99%
“…In arid regions, abiotic factors like high irradiance, heat, water shortage, salt stress, as well as sand burial could be the main stress factors. Bruelheide et al (2010) indicated that the terrain of Cele region appears to have higher altitude in the south and lower altitude in the north, additionally the ground water level slowly increases from 17.15 m at the Cele County to 3.5 m at the light desertification region. In addition, the biennial plants of A. sparsifolia with strong, deep roots, on average, have approximate 6-m length and 17 ramets, so that the root could reach the ground water.…”
Section: Effects Of Elevated Temperature On Psiimentioning
confidence: 96%
“…There are different types of vegetation, composed of different proportions of a few woody species, which differ in their hydrological niche with respect to distance to the groundwater table (Bruelheide et al, 2010). Maximum distances to the groundwater table of mature stands have been found to reach 17.5 m , distances at dune tops can even attain 24 m (Gries et al, 2003).…”
Section: Introductionmentioning
confidence: 98%